Care bundles for acute kidney injury: a balanced accounting of the impact of implementation in an acute medical unit. Issue 4 (18th December 2018) - Logan, Rachael; Davey, Peter; Davie, Alison; Grant, Suzanne; Tully, Vicki; Valluri, Achyut; Bell, Samira
Abstract : In 2009, a National Confidential Enquiry into Patient Outcome and Death report detailed significant shortcomings in recognition and management of patients with acute kidney injury (AKI). As part of a national collaborative to reduce harm from AKI, the Scottish Patient Safety Programme developed two care bundles to improve response ('SHOUT') and review ('BUMP') of AKI. Baseline data from eight patients with AKI on the acute medical unit (AMU) in Ninewells Hospital showed 62% compliance with SHOUT. However, most patients were transferred from AMU within 24 hours so BUMP could not be assessed. Our aim was to achieve >95% compliance with SHOUT on AMU within 2 months. The content of the SHOUT bundle was condensed onto a sticker for the case notes, which was implemented using Plan-Do-Study-Act cycles. Compliance was assessed weekly and feedback obtained from stakeholders concerning their opinion of the sticker, SHOUT bundle and care bundles in general. Use of the sticker was 27% in week 1 but fell to 5% by week 4. Compliance with the bundle varied from 45% to 60% and was only slightly improved by use of the sticker (OR 1.58, 95% CI 0.39 to 6.42). Staff found the sticker burdensome and did not agree that all elements of SHOUT were equally important. This opinion was supported by finding that their compliance with sepsis and hypovolaemia recommendations was 91%–100% throughout, whereas urinalysis was documented in only 55%–63% of patients. Several staff mentioned 'bundle fatigue' and on one day we identified 22 other care bundles or structured improvement forms in AMU. We concluded that the AMU staff had legitimate concerns about the SHOUT care bundle and that our intervention was demotivating. Overcoming bundle fatigue will not be a simple task. We plan to work with staff on integrating AKI into patient safety huddles and on using modelling and recognition of good practice to improve motivation.